"Só vencem os fortes": a barbárie do trote na educação agrícola - Silva, Rosiane Maria da (2015)
SILVA, R.M. “Only the Strong Win”: The Hazing Barbarism in Agricultural Education. Dissertation (Doctorate in Education) - Programa de Pós-Graduação em Educação da UFSCar, Federal University of São Carlos, São Carlos, 2015. Traditional hazing practices in educational institutions date back to the 15th century in the first European universities and continue to the contemporary college hazing. Through literature review, gaps have been pointed related to this subject in the context of Brazilian agricultural schools. Adorno state that to “fight barbarism", hazing used in the German holocaust should be avoided. Based on this perspective, this research discusses the revival of the Nazi-fascist authoritarian personality nowadays. The research hypothesis is that the institutional culture medium in an agricultural school supports hazing barbarism. This study aimed to analyze the traditional hazing in the former Colégio Agrícola de Uberlândia (Agricultural College of Uberlândia) from 1969 to 1985, investigate the relations between institutional culture, hazing and the development of students' subjectivity in a hazing context. Therefore, the theoretical ground and discussions were based on the writings of Adorno, Horkheimer and collaborators about the "Authoritarian Personality Syndrome" and on Adorno's and Freud’s sociological works. The research methodology consisted of the semistructured interview with 10 participants. Empirical data were compared with the theory. The hypothesis was confirmed: the culture medium of Colégio Agrícola carries features that supports hazing. Five categories were applied to the interviews. The data were submitted to content and document analysis. It was observed that a committee consisted of students and public servants institutionalized hazing. Traditional hazing such as nicknaming and mud bathing were pointed. Due to hazing violence that resulted in some serious injuries, the hazing committee was disbanded in 1983. The institutionalized hazing expressed prejudices and the thinking of the ticket, by means of group exclusions and derogatory nicknames. The culture of machismo was detected in the viewpoint of student and hazing, masculine institutions. The Freudian ground to the concept of mass based the evidence that the student leaders were the ablest to conduct hazing; however, their involvement was reinforced by hazing institutional elements. The academic community was divided into segments in the context of hazing, but on the in general it was widely institutionalized. The conclusion is that hazing was an institutional phenomenon in Colégio Agricola de Uberlandia. Furthermore, hazing served students as a training for academic life and job market, by means of Taylorist and Fordist Technical Education. Hazing, courses and the teaching and learning processes of Technical Education during the time range under consideration was in compliance with military principles. In the last stage of this research, a CPI (Parliamentary Inquiry Commission) set up to investigate hazing in São Paulo universities revealed injuries and sexual abuses. To definitely stop hazing, it depends on a change in mind of students and leaders who disseminate prejudice and barbarism. Thus, the idea that "only the strong win", that shapes the human subjectivity and supports the hazing practices in the Technical Education, must be understood and immediately fought.